Evaluasi dan Perbaikan User Experience Aplikasi Perangkat Bergerak Sistem Informasi Karyawan menggunakan Metode Usability Testing dan User Centered Design (Studi Kasus: Teladan Prima Group) - Farras Almay Renando; Agi Putra Kharisma; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Mobile Apps â€œTeladan Appsâ€ is an application that has been developed to give employee access more easily and comfortably for work activity to employees in Teladan Prima Group companies engaged in plantations and Palm Oil factories in this pandemic situation without leaving the house. As a new product, the development team from the application Teladan App hasn't evaluated the User Experience. This research uses the Usability Testing method to identify usability problems. This method can help to find the chance and understand the activity and preferences in using a product (Moran, 2019). The evaluation process and upgrading application â€œTeladan Appsâ€ will use User-Centered Design (UCD) which is an approach way in the making designs that puts the user at the center of the design. The result of this evaluation and examination using the Usability Testing method in the prototype of Teladan Application, the application obtained a value of 91%. The result accomplished from the dissemination UEQ questionnaire in the second step examination represent 6 aspects which is the attractiveness with an average of 2.29, the perspicuity with an average of 2.21, the efficiency with an average of 2.19, the dependability with an average of 1.99, the stimulation with an average of 2.14, and the novelty with an average of 1.90. From the evaluation result for all aspects have a positive grade.